2020
DOI: 10.1029/2020gl089509
|View full text |Cite
|
Sign up to set email alerts
|

Volcanically Induced Transient Atmospheres on the Moon: Assessment of Duration, Significance, and Contributions to Polar Volatile Traps

Abstract: A transient lunar atmosphere formed during a peak period of volcanic outgassing and lasting up to about~70 Ma was recently proposed. We utilize forward-modeling of individual lunar basaltic eruptions and the observed geologic record to predict eruption frequency, magma volumes, and rates of volcanic volatile release. Typical lunar mare basalt eruptions have volumes of~10 2-10 3 km 3 , last less than a year, and have a rapidly decreasing volatile release rate. The total volume of lunar mare basalts erupted is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 39 publications
(91 reference statements)
0
39
0
Order By: Relevance
“…In addition to impacts, volcanic activity is suspected to be an important pathway for the transport of volatiles to the lunar surface (Milliken & Li, 2017; Needham & Kring, 2017; Saal et al, 2008; Wilson & Head, 1981). We applied new eruption frequency estimates from Head et al (2020) to calculate the delivery of volcanically outgassed water to the poles (the supporting information). Water formed from interactions between the regolith and solar wind was ignored in this work because it likely contributes many orders of magnitude less water than asteroids and volcanism (Hurley et al, 2017; Lucey et al, 2020) and may be outweighed by loss processes including UV photolysis and solar wind sputtering at the very surface (Farrell et al, 2019).…”
Section: Stratigraphy Simulationsmentioning
confidence: 99%
“…In addition to impacts, volcanic activity is suspected to be an important pathway for the transport of volatiles to the lunar surface (Milliken & Li, 2017; Needham & Kring, 2017; Saal et al, 2008; Wilson & Head, 1981). We applied new eruption frequency estimates from Head et al (2020) to calculate the delivery of volcanically outgassed water to the poles (the supporting information). Water formed from interactions between the regolith and solar wind was ignored in this work because it likely contributes many orders of magnitude less water than asteroids and volcanism (Hurley et al, 2017; Lucey et al, 2020) and may be outweighed by loss processes including UV photolysis and solar wind sputtering at the very surface (Farrell et al, 2019).…”
Section: Stratigraphy Simulationsmentioning
confidence: 99%
“…Endogenic outgassing of primordial water is more likely in the distant past than in recent history (Needham and Kring 2017;Deutsch et al 2019;Head et al 2020). At this point, the major source of molecular water has not been determined on either Mercury or the Moon.…”
Section: Sourcesmentioning
confidence: 96%
“…Needham and Kring (2017) estimated that volcanically derived volatiles alone, degassed during mare basalt forming eruptions, could account for all currently observed hydrogen deposits in lunar PSRs. However a more recent study by Head et al (2020) suggests volatile-rich impactors to be the main source of polar volatiles rather than volcanically derived volatiles. Crider and Vondrak (2002) showed that water deposits implanted by the solar wind proton flux within 100 Ma could also account for all hydrogen detected by the Lunar Prospector Neutron Spectrometer (LPNS; Feldman et al, 1998).…”
Section: Volatile Sources Migration and Cold Trappingmentioning
confidence: 99%
“…However a more recent study by Head et al. (2020) suggests volatile‐rich impactors to be the main source of polar volatiles rather than volcanically derived volatiles. Crider and Vondrak (2002) showed that water deposits implanted by the solar wind proton flux within 100 Ma could also account for all hydrogen detected by the Lunar Prospector Neutron Spectrometer (LPNS; Feldman et al., 1998).…”
Section: Introductionmentioning
confidence: 99%